Social support and outcomes in older adults with lung cancer. Issue 2 (March 2022) - Chambers, Andrew; Damone, Emily; Chen, Yi Tang; Nyrop, Kirsten; Deal, Allison; Muss, Hyman; Charlot, Marjory
Abstract: Background: Insufficient social support is associated with increased mortality among older adults. Lung cancer is primarily a disease of older adults and is the leading cause of all cancer deaths. We assessed the association of social support with outcomes among older adults with lung cancer. Materials and Methods: Adults age 65 and older with lung cancer with a completed geriatric assessment (GA) were assessed. Emotional social support (ES) and tangible (material, instrumental) support (TS) measures and patient characteristics were obtained from the GA. The electronic health record was used to extract clinical variables. Simple linear regression models evaluated the association between social support scales with patient and clinical factors. Results: 79 adults were assessed. White race was positively associated with ES score (p=.04), while higher BMI (p=.03), depression (p=.03) and anxiety (p=.02) were associated with worse ES. Higher BMI was associated with higher/better TS score (p=.02) while living alone was associated with lower/worse TS score (p=.03). Completion of platinum-based doublet chemotherapy with immunotherapy as planned was associated with higher ES scores (p=.02) and higher TS scores (p=.02). Disease progression was associated with lower ES scores (p=.03). Conclusion: Social support may influence clinical outcomes in older adults with lung cancer. As lung cancer often portends to poor prognosis, social support may be an important prognostic indicator.